PELATIHAN DAN PENDAMPINGAN TAKMIR MASJID DI KELURAHAN FOBAHARU KECAMATAN KOTA TIDORE UTARA KOTA TIDORE KEPULAUAN - Sugianto, Hendi; Aksan, Sahjad M; Abbas, Nurhasnah; Marengke, Musa (Institut Agama Islam Negeri Ternate, 2023)
Mosques have a very strategic role in the life of Muslims. More than just a place of worship, the mosque also functions as a center for various religious and community activities. Training and mentoring of mosque takmir as a community service activity carried out by lecturers of the Islamic Religious Education study program FTIK IAIN Ternate in the mosque of Fobaharu Village, North Tidore City District, Tidore Islands City aims to provide an understanding to mosque takmir administrators about the importance of management structure and mosque management. The methods used are: first, lecture method, second, practicum method; and third, question and answer method. This service activity is considered successful based on the full participation of all 20 invited participants who attended. The participants felt that this activity was very useful because it helped increase the prosperity of the mosque through effective management and a proportional board structure, and encouraged their commitment to play an active role in prospering the mosque.Keywords: Mosque, Training, Mentoring, Mosque Management .